Understanding the Concept of Intelligent Operations Through ELPSA Learning when Learning From Home - Ramuni A (Eduvest - Journal of Universal Studies, 2021)
This Scientific Review in the form of best practice Learning the ELPSA (Experience, Language, Picture, Symbol, Application) model examines learning as an active process where students construct their own way of understanding things through individual thought processes and social interactions with others in BDR activities. In this BDR activity, LKPD is used. This Scientific Review (Best Practice) activity aims to improve understanding of the concept of integer operations through ELPSA learning for class VIIA students of SMPN 5 Sanggau. This activity is carried out in the 2021/2022 school year, to be precise in July. The success criteria set by the researchers are student activities during the BDR learning process in the good category, at least 80% of the number of students can reach the KKM which is 70. The results of this scientific review show that students' understanding of learning integer operations through ELPSA learning when BDR has been achieved by the success criteria shown in the post test results. In more detail, the percentage of achievement of the success criteria is as follows: 1) student activities during the learning process are in the good category, 2) There is an increase in the percentage of students who have reached the KKM by 31.25% from pre-test 56.25% to 87.5% in post test. From the results of the study, it can be concluded that ELPSA learning is effective in increasing the understanding of the concept of integer operations during BDR.